EFFECTIVE ESTABLISHMENT OF SUPERVISORY BOARD ACTIVITY IN STATE-OWNED ENTERPRISES: FAVORABLE MECHANISMS AND MUTUAL COOPERATION (European Journal of Economics, Finance and Business Development, 2025)
This article explores the effective establishment and functioning of supervisory board activities within state-owned enterprises (SOEs). Emphasizing the importance of governance frameworks, the discussion highlights favorable mechanisms that can enhance transparency, accountability, and performance in SOEs. The article also examines the role of mutual cooperation between government entities, the private sector, and various stakeholders in optimizing board effectiveness. By drawing on international best practices and case studies, the work provides actionable recommendations for strengthening supervisory boards in Uzbekistan and similar contexts, ultimately contributing to improved operational efficiency and sustainable development.